The Implementation of Maqashid Shari’ah as the Tool of Data Analysis in Islamic Economic Law Research - Misno BP, Abdurrahman; Wijaya, Rusdiana Priatna (AL- IKTISAB Journal of Islamic Economic Law, 2018)
Data analysis in research of the study becomes urgent; it is the key for a successfulresearch. Using wrong of data analysis will result on the error conclusion. Therefore,choosing the right analysis to examine a problem in research is an important thing to beconsidered. Maqashid Shari’ah is the purpose and objective of Shari’ah that was initiated bythe earlier Muslim scholars that put fondation of maqashid al-khamsah which is formulatedin the protection of; religion, soul, mind, heredity and property. How to make maqashidShari’ah as a tool in analyzing Islamic economic research especially sharia economic law?The method used in this research is grounded theory which the study of maqashid Shari’ahdeveloped into an analysis in qualitative research. The data used are thoughts sourced fromexperts who discuss about this theme. It is further developed into a measuring tool in theanalysis of the study. The result of data in this research is that maqashid Shari’ah is verysuitable to be the analysis tool in sharia economic law research. It can be formulated in itsgeneral nature that is maqashid Shari’ah taken generally from some maqashid experts. Andalso turn out a single thought about maqashid Shari’ah used as an analysis tool.